2014
DOI: 10.1099/ijs.0.056614-0
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces barkulensis sp. nov., isolated from an estuarine lake

Abstract: The taxonomic position of a novel actinomycete, strain RC 1831 T , isolated from the sediment of a fish dumping yard at Barkul village near Chilika Lake, Odisha, India, was determined by a polyphasic approach. Based on morphological and chemotaxonomic characteristics the isolate was determined to belong to the genus Streptomyces. The phylogenetic tree based on its nearly complete 16S rRNA gene sequence (1428 nt) with representative strains showed that the strain consistently falls into a distinct phyletic line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…1 Scanning electron micrograph of isolate GY1 T on yeast extract-malt extract agar after 14 days at 28°C showing rough to warty ornamented spores in spiral chains. Indeed, similar fatty acid profiles have been reported for the type strains of S. atacamensis, S. barkulensis and S. radiopugnans (Mao et al 2007;Santhanam et al 2012;Ray et al 2014). Similar fatty acid patterns were shown to be present in S. fenghuangensis NRRL B-24801 T and S. S. nanhaiensis KCTC 19401 T although quantitative differences were found in the proportions of the major components and small qualitative differences in some fatty acids found in minor and trace amounts (Supplementary Table S1), results in good agreement with previous fatty acid analyses of these organisms (Zhu et al 2011;Tian et al 2012).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…1 Scanning electron micrograph of isolate GY1 T on yeast extract-malt extract agar after 14 days at 28°C showing rough to warty ornamented spores in spiral chains. Indeed, similar fatty acid profiles have been reported for the type strains of S. atacamensis, S. barkulensis and S. radiopugnans (Mao et al 2007;Santhanam et al 2012;Ray et al 2014). Similar fatty acid patterns were shown to be present in S. fenghuangensis NRRL B-24801 T and S. S. nanhaiensis KCTC 19401 T although quantitative differences were found in the proportions of the major components and small qualitative differences in some fatty acids found in minor and trace amounts (Supplementary Table S1), results in good agreement with previous fatty acid analyses of these organisms (Zhu et al 2011;Tian et al 2012).…”
Section: Resultssupporting
confidence: 78%
“…Isolate GY1 T , unlike the type strain of S. fenghuangensis, its nearest phylogenetic neighbour, was found to form spores in spiral chains and to use sucrose, trehalose and xylose as sole carbon sources. Similarly, isolate GY1 T can be distinguished from the type strain of S. barkulensis using a combination of phenotypic features acquired using the same standard taxonomic methods (Ray et al 2014). Similarly, isolate GY1 T can be distinguished from the type strain of S. barkulensis using a combination of phenotypic features acquired using the same standard taxonomic methods (Ray et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Streptomyces fenghuangensis NRRL B-24801 T contained diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol mannoside, phosphatidylinositol, one unidentified aminolipid, two unidentified phospholipids and an unidentified glycolipid (Fig. S1), which is similar to the polar lipids of 'Streptomyces mangrovicola' GY1 (=NCIMB 14980) (Yousif et al, 2015), Streptomyces barkulensis RC 1831 T (=JCM 18754 T ) (Ray et al, 2014) and Streptomyces radiopugnans R97…”
mentioning
confidence: 91%
“…In addition, the presence of lysophosphatidylethanolamine in the phospholipid profile was distinctive from Streptomyces fenghuangensis NRRL B-24801 T and related type strains ( Fig. S1; Yousif et al, 2015;Ray et al, 2014;Mao et al, 2007). According to Ray et al (2014), growth of Streptomyces barkulensis RC 1831 T was not observed on ISP2 agar medium.…”
mentioning
confidence: 95%
See 1 more Smart Citation